Environmental, manpower and financial analysis of locust control in South Africa - Peters, Susanna Magdelena (University of the Free State, 2000)
The brown locust, Locustana pardalina (Walker), has regularly recurring outbreaks in the region Karoo region of South Africa. The endemic region comprises an area of approximately 40 million hectares. The locusts in the gregaria phase cause considerable damage to natural pastures and is in direct competition with stock farming. The National Department of Agriculture administers locust control campaigns. Trained volunteers (supervisors and assistants) in the locust districts conduct locust control campaigns and are remunerate for their efforts. Any sustainable agricultural setup and pest control should adhere to the following three criteria: environment, manpower and financial resources. This study was aimed at analyzing the 1996/97 locust control campaign, with the emphasis on the De Aar, Hanover, Hay and Postmasburg locust districts, based on these three criteria. The project was divided into two main parts: a component analysis for managerial purposes and a spatial analysis (in ArcView-GIS) for operational purposes. The component analysis was done on supervisor level within the districts and the spatial analysis was done on both farm and district levels. Great variation existed between the supervisors and districts analysed in all three criteria. The highest number of bands and swarms was controlled in the Hanover district (5392), followed by Hay (1 961) De Aar (1 519) and Postmasburg (859). The supervisors in the De Aar district controlled a higher percentage of hopper versus adult locusts (87 vs. 13 %). The opposite was encountered in Hanover (28 vs. 72 %), Hay (32 vs. 68 %) and Postmasburg (45 vs. 55 %). The highest total area (Ha) bands and swarms was sprayed in the De Aar district (Il 410), followed by Hanover (9 493), Hay (5 054) and Postmasburg (2 816). Locusts had the highest impact on grazing in the Hanover district. Effective control operations resulted in small areas of each district being sprayed: De Aar (2,13 %), Hanover (2,63 %), Hay (0,40 %) and Postmasburg (0,16 %). An early warning system to facilitate locust control is possible with the incorporation of reliable biotic and abiotic data. Dissimilarities in manpower utilisation were evident through the area (Ha) and amount of pesticide sprayed per assistant per day in the various districts. The highest numbers of supervisor (800) and assistant (2 039) days were recorded in the Hanover district and the lowest numbers (172 vs. 129) were recorded in the Postmasburg district. A geographic information system enables visual monitoring of job creation and socio-economic implications of locust control. The pesticide and travelling expenditure accounted for most of the expenses. The expenses per hectare (RlHa) were the highest in the Hay district (70,07) and the lowest in Postmasburg (23,17). The actual financial damage caused by the locusts was much lower than the potential financial loss. Investment return factors (IRF's) of more than one hundred were achieved in all the districts. The integrated operational and management information system enables visual access to extensive locust control data. This information system eases management by facilitating proper planning within and among campaigns.

Die bruinsprinkaan (Locustana pardalina, Walker) het gereelde uitbrake in die Karoostreek van Suid-Afrika. Die endemiese gebied beslaan 'n area van ongeveer 40 miljoen hektaar. Die sprinkaan in die gregaria fase veroorsaak ernstige skade aan natuurlike wieding en is in direkte kompetisie met veeboerdery. Die Nasionale Departement van Landbou behartig die sprinkaanbeheerveldtogte. Opgeleide vrywilligers (opsigters en arbeiders) in die sprinkaandistrikte voer die veldtogte uit en word daarvoor betaal. Enige volhoubare landboustelsel en plaagbeheer moet aan die volgende kriteria voldoen: omgewing, mannekrag en finansies. Hierdie studie het die 1996/97 sprinkaanveldtog geanaliseer met die fokus op die De Aar, Hanover, Hay en Postmasburg sprinkaandistrikte en gebaseer op die drie kriteria van volhoubaarheid. Die projek was in twee hoof dele verdeel: 'n komponentanalise vir bestuursdoeleindes en 'n ruimtelike analise (in ArcView-GIS) vir operasionele doeleindes. Die komponentanalise was op opsigtervlak in distrikte en die ruimtelike analise was op beide plaas- en distriksvlak gebaseer. Daar was groot variasie tussen die opsigters en die distrikte geanaliseer ten opsigte van al drie kriterië. Die grootste aantal voetganger- en vlieërswerms is in die Hanover distrik (5 392) beheer, gevolg deur Hay (1 961), De Aar (l 519) en Postmasburg (859). Die opsigters het in De Aar die hoogste persentasie voetgangers versus volwasse sprinkane beheer (87 vs. 16 %). Die teenoorgestelde is in Hanover (28 vs. 72 %), Hay (32 vs. 68 %) en Postmasburg (45 vs. 55 %) aangetref. Die grootste totale area (ha) waarop voetgangers en volwasse sprinkane beheer is, was in De Aar (11 410), gevolg deur Hanover (9 493), Hay (5 054) en Postmasburg (2 816). Sprinkane het die grootste impak op weiding in die Hanover distrik gehad. Klein areas in elke distrik is bespuit as gevolg van die effektiewe beheermaatreëls: De Aar (2,13 %), Hanover (2,63 %), Hay (0,40 %) en Postmasburg (0,16 %). As betroubare biotiese en abiotiese data geinkorporeer word, kan 'n vroeëwaarskuwingstelsel saamgestel word wat behulpsaam is met sprinkaanbeheer. Verskille in die gebruik van mannekrag in die distrikte was duidelik deur die area (Ha) en hoeveelheid plaagbeheermiddels wat deur die assistente per dag bespuit is. Die hoogste aantal opsigter- (800) en assistentdae (2 039) was opgeteken in Hanover en die laagste (172 vs. 129) was in die Postmasburg distrik. 'n Geografiese inligtingstelsel maak die visuele monitering van werkskepping en die sosioekonomiese implikasies van sprinkaanbeheer moontlik. Die koste van plaagbeheermiddels en vervoerkoste het die grootste komponente van die uitgawes uitgemaak. Die uitgawes per hektaar (RlHa) was die hoogste in die Hay distrik (70,07) en die laagste in Postmasburg (23,17). Die werklike skade wat deur die sprinkane aangerig is, was baie laer as die potensiële finansiële skade. Teenprestasiefaktore van meer as een honderd is in al die distrikte bereik. Die geïntegreerde operasionele en bestuursinligtingstelsel verskaf visuele toegang tot uitgebreide sprinkaanbeheerdata. Hierdie inligtingstelsel vergemaklik bestuur deurdat dit behoorlike beplanning in en tussen veldtoë meebring.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2000
Keywords: Locustana pardalina; Locust control; Operational and management information system; Geographic information system; Cost benefit analysis; Locusts -- Control -- South Africa -- Karoo; Sustainable agriculture -- South Africa -- Karoo; Management information systems